Long-term outcomes of oncoplastic breast resection with local perforator flaps - Iu. S. Shatova; N. A. Maksimova; I. N. Vashchenko; N. A. Shevchenko; E. N. Chernikov (ABV-press, 2022)
Background. Oncoplastic breast resections with perforator flaps are relatively common now; however, many studies demonstrate contradictory results, especially in terms of long-term outcomes.Objective: to assess short-term and long-term outcomes of oncoplastic breast resection with defect repair using perforator flaps.Materials and methods. This study included 62 breast cancer patients who underwent oncoplastic breast resection with defect repair using local perforator flaps, including lateral intercostal artery perforator (LICAP) flaps (40.3 %), lateral thoracic artery perforator (LTAP) (19.4 %), anterior intercostal artery perforator (AICAP) (27.4 %), and medial intercostal artery perforator (MICAP) (12.9 %) flaps. The assessment of oncological, functional, and aesthetic outcomes was performed in patients who were followed-up for at least a year (n = 57). Mean follow-up time was 26.5 months (range: 14-38 months).Results. The following complications were registered among the patients studied: seroma in the area of excised primary tumor (8.1 %), insufficient blood supply of the flap that caused focal lipofibrosis/liponecrosis (3.2 %), positive resection margin (3.2 %), low position of the submammary fold (11.3 %), locoregional recurrence (0 %), generalized process (3.5 %). All women evaluated their functional and aesthetic result as good or excellent. According to BCCT.core 3.0, 91.3 % of patients achieved good and excellent results.